Islam, Ethics and Modern Medicine: From Theory to Medical Practice: A Narrative Review - Sheikh Mohd Saleem; Shah Sumaya Jan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
Islam arose from the same Semitic soil that gave rise to Judaism and Christianity. As stated in the Declaration of Faith, its most fundamental idea is monotheism. For Muslims, holy law is an all-encompassing entity that concerns every aspect of human life. Many Ulema has concluded that the concept of a â€œconsensus decreeâ€ is preferable in the circumstances needing specialist understanding. These consensus panels for medical choices often include a broad and diversified representation. The decision-making process is frequently transparent, allowing members of the greater community to scrutinize the arguments presented. Before providing culturally sensitive treatment, a fundamental level of cultural awareness is essential. We simplified and highlighted key themes in Islamic medical ethics in this study. Despite the fact that this is a preliminary study, we believe the findings will assist physicians in better understanding their Muslim patients.